Investigation of the ethical practice in medication process among nurses - M.R Tefag; A.R Nikbakht Nasrabadi; A Mehran; N Dinmohammadi (Tehran University of Medical Sciences, 2005)
Introduction: Caring is the essence of nursing and medication process is an important part of nursing related interventions in the health care systems. Medical and/or nursing errors can lead to severe problems for both patients and nursing system. The purpose of this study was to investigate the ethical practice in medication process among nurses working in selected hospitals related to Tehran University of Medical Sciences.          Materials and Method: This study is a descriptive-analytic research. Samples of the study were 305 nurses employed in adult units of selected hospitals. The research data gathering tools were a checklist and a questionnaire. Questionnaire included questions about demographic data and errors in medication process. Checklist included 17 questions related to expected behaviors regarded medication process. The researcher first completed the questionnaire and then the checklist was completed on two separate occasions at least 15 days apart. The data were analyzed using descriptive and analytic statistics such as Chi square, Fisher exact test and Pearson correlation coefficients. Results: The majority of subjects were 26-35 years old, female and single. About half of nurses (49.6%) had undesirable performance in process of medication. Ethical practice had a significant correlation with type of ward (p=0.005), the mean number of occupied beds in a week (p=0.000), number of co-workers in the shift (p=0.001), educating (p=0.037), satisfaction with place of work (p=0.0043) and technical possibilities in the ward (p=0.029). Conclusion: According to the results, the majority of nurses had an undesirable performance in medication process. It is suggested that managers, program planners and nursing teachers pay more attention to ethical practice in medication process in order to enhance performance of nurses in this field.